RELATIONSHIP BETWEEN BLOOD SUGAR LEVELS AND THE RESULTS OF ACID-FAST BACILLA EXAMINATION IN PULMONARY TUBERCULOSIS PATIENTS - Muhammad Nazirul Irfan; Siti Rahmalia Hairani Damanik; Darwin Karim (Universitas Karya Husada Semarang, 2024)
Introduction: Tuberculosis (TB) is a highly contagious disease and a leading cause of morbidity and mortality worldwide. When Mycobacterium tuberculosis enters the body of an individual with elevated blood glucose levels, it creates a favorable environment for bacterial growth and proliferation. Objective: This study aimed to investigate the correlation between blood glucose levels and acid-fast bacilli (AFB) smear results in pulmonary tuberculosis patients at Arifin Achmad General Hospital, Pekanbaru. Methods: This study employed a retrospective analytical correlational design using secondary data from medical records. A total sample of 51 cases was analyzed using total sampling. Data was collected using an observation sheet and analyzed using Fisher's exact test. Results: A majority of the respondents (43%) had blood glucose levels exceeding 125 mg/dl, and a significant proportion (76.5%) had positive AFB smears. The Fisher exact test revealed a significant correlation between blood glucose levels and positive AFB smear results (p < 0.05). Conclusion: This study demonstrates a significant association between blood glucose levels and AFB smear results in pulmonary tuberculosis patients at Arifin Achmad General Hospital, Pekanbaru.